Choledochoduodenostomy versus T-tube drainage in patients have stones in common bile duct with risk factors of post-operative missed stones - Ali, Mohamed M.; Helmy, Mena Zarif; Gomaa, Emad (International Surgery Journal, 2019)
Background: Residual or missed stones of common bile duct (CBD) and ascending cholangitis after CBD exploration are major biliary surgery problems. Repeated biliary tract interventions for correction of complications are catastrophic on both patients and surgeons. Methods: This is a prospective study of 83 patients which compares two methods for surgical management of CBD stones between June 2016 to May 2018. Group I included 43 patients who were managed by CBD exploration followed by insertion of T tube, the risk factors of the incidence of missed retained stone in CBD were multiple stones in CBD and hugely dilated CBD (>15 mm).The second method was choledochoduodenal anastomosis for patients having the same previous risk factors (Group II) which included 40 patients. Postoperative follow up was for 12 to 18 months. Results: In group I, 6 patients developed residual stones in CBD, reoperation was required for 3 of them and endoscopic retrograde cholangiopancreatography with sphincterotomy for another 3 patients, while in the other group (group II) 2 patients suffered from ascending cholangitis and are managed conservatively. No missed or residual CBD stones were developed and no patients need reoperation. Conclusions: With choledochoduodenostomy in patients with multiple CBD stones or markedly dilated CBD the incidence of missed or retained stones in CBD was reduced.